Tembang Macapat Melalui Novel Canting Karya Fissilmi Hamida (Kajian Estetika Resepsi) - Sri Suharti (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
The purpose of this study is to reveal how Fissilmi Hamida responds to the song Macapat through his novel entitled Canting. This research is a qualitative research with a reception aesthetic theory approach. The results showed that Fissilmi Hamida confirmed the meaning contained in the macapat song. The song is Mijil which is interpreted as a way of life so that someone is useful in life. Kinanthi is interpreted as the formation of human identity which means it requires guidance and guidance. Asmaradana is interpreted as the basis of Javanese society in living a married life so that it is lasting and happy.  Keywords: Macapat; Aesthetic Reception; Novel